Ritual and Narrative: Theoretical Explorations and Historical Case Studies - Ahn, Gregor; Nünning, Vera; Rupp, Jan (Kultur- und Medientheorie, 2013)
Biographical note: Vera Nünning (PhD) is Chair of English Philology at the English Department of Heidelberg University, Germany. Jan Rupp (PhD) is a postdoctoral research assistant at the English Department of Heidelberg University, Germany. Gregor Ahn (PhD) is Chair of Religious Studies at Heidelberg University, Germany.